Combined use of field observations and SAR interferometry to study ice dynamics and mass balance in Dronning Maud Land, Antarctica - Dietrich, Reinhard; Metzig, Robert; Korth, Wilfried; Perlt, James (Polar Research, 1999)
In the region of the Schirmacheroase (71 °S, 12°E) various geodetic and glaciological research activities have been carried out in the last decade. Several times three geodetic-glaciological traverses were undertaken to study ice velocity, accumulation and ablation, and ice surface height changes. Repeated ground surveys show a significant decrease in surface heights by about 15 cm/y for a large blue-ice area. This paper presents the first interferometrically derived ice velocity field of the inland ice close to the Schirmacheroase. The interferometric analysis of the synthetic aperture radar (SAR) data is performed in combination with ground-based information. Since only ERS-1&2 tandem mission image couples are available for this region a digital elevation model (DEM) is used to remove the effect of topography. Ice velocities up to 100 m/y are proved interferometrically for this part of the inland ice.
Keywords: Dronning Maud Land; geodesi; glasiologi; innlandsis

Variability in snow layering and snow chemistry in the vicinity of two drill sites in western Dronning Maud Land, Antarctica - Hansson, Margareta; Holmlund, Per; Karlöf, Lars; Stenberg, Malin (Annals of Glaciology, 1999)
As part of the pre-site survey in Dronning Maud Land for the European Project for Ice Goring in Antarctica (EPICA), the spatial variability of snow-layer thickness and snow chemistry was studied at two geographically different ice-core drill sites. The study aimed to quantify error bars on accumulation rates derived from firn and ice cores. One site is located on the polar plateau at Amundsenisen (76° S, 8° W) and the other in the coastal area at Maudheimvidda (73° S, 13° W). Medium-deep ice cores (100 m) and shallow firn cores (10-20 m) were drilled and snow pits (0.5-2 5 m) were dug at each site. At Amundsenisen a large (16 m x 6 m x 2.5 m deep) snow pit was dug. Snow structure in this large snow pit was mapped using optical surveying equipment, and photographically documented. Samples for analysis of nine ions and oxygen isotopes were collected along one depth profile. Density and in situ electrical conductivity measurements were made along three depth profiles! Snow-layer variability was studied in two different areas and at two different scales. At a regional scale, measured by snow-radar soundings, the variability was 8% on the polar plateau and 45% in the coastal area. The variability at a micro-scale in the large snow pit was 9%. The results indicate that ice cores from the polar plateau are more representative for a larger area than ice cores drilled in the coastal area There is no doubt that there are significant error bars on high-resolution accumulation data received from firn and ice cores, especially from the coastal area, but averaging over tens of years reduces the error in accumulation estimates.
Edition: 2017/09/14 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fysisk geografi; geokjemi; glasiologi; iskjerner; paleoklimatologi

Predicted present-day evolution patterns of ice thickness and bedrock elevation over Greenland and Antarctica - Huybrechts, Philippe; Le Meur, Emmanuel (Polar Research, 1999)
This paper discusses predicted evolution patterns of present-day changes of ice thickness, surface elevation, and bedrock elevation over the Greenland and Antarctic continents. These were obtained from calculations with dynamic 3-D ice sheet models which were coupled to a visco-elastic solid Earth model. The experiments were initialized over the last two glacial cycles and subsequently averaged over the last 200 years to obtain the current evolution. The calculations indicate that the Antarctic Ice Sheet is still adjusting to the last glacial-interglacial transition yielding a decreasing ice volume and a rising bedrock elevation of the order of several centimetres per year. The Greenland Ice Sheet was found to be close to a stationary state with a mean thickness change of only a few millimetres per year, but the calculations revealed large spatial differences. Predicted patterns over Greenland are characterized by a small thickening over the ice sheet interior and a general thinning of the ablation area. In Antarctica, almost all of the predicted changes are concentrated in the West Antarctic Ice Sheet, which is still retreating at both the Weddell and Ross Sea margins. Over most of both ice sheets, the model indicates that the surface elevation trend is dominated by ice thickness changes rather than by bedrock elevation changes.
Keywords: Antarktis; glasiologi; innlandsis; polarområdene

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

Accumulation and proxy-temperature variability in Dronning Maud Land, Antarctica, determined from shallow firn cores - Isaksson, Elisabeth; van den Broeke, Michiel R; Winther, Jan-Gunnar; Karlöf, Lars; Francis Pinglot, Jean; Gundestrup, Niels (Annals of Glaciology, 1999)
During 1996-97 a European Project for Ice Goring in Antarctica (EPIGA) pre-site surveying traverse worked in the area between 70° S, 5° E and 75° S, 15° E in Dronning Maud Land. We present data obtained from 10 and 20 m deep firn cores drilled between the coast and 600 km inland (to 3450 m a.s.l.). The cores were analyzed for electrical conductivity measurements and total β activity to obtain accumulation data between known time horizons. In addition, some of the cores were analyzed for oxygen isotopes. Annual accumulation varies from 271 mm we. at Fimbulisen to 24 mm we at 2840 m a.s.l. Accumulation at core sites 2400-3000 m a.s.l. has increased by 16-48% since 1965 compared to the 1955-65 period. However, the core sites above 3250 m a.s.l. and one core location on the ice shelf show a decrease during the same period. Furthermore, no change can be detected at the most inland site for the period 1815-1996. In all the cores the last few years seem to have been some of the warmest in these records.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

A study of the ice dynamics of Jutulstraumen drainage area, by means of remote sensing - Rolstad, Cecilie; Hagen, Jon Ove; Østen, Kristoffer; Tonning, Tore; Semb, Svein Ingar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Antarktis; NARE 1997/98; akkumulasjon; glasiologi; innlandsis; klimaendringer

Climatic trend and the retreat and disintegration of ice shelves on the Antarctic Peninsula: an overview - Skvarca, Pedro; Rack, Wolfgang; Rott, Helmut; Ibarzábal Donángelo, Teresa (Polar Research, 1999)
Observation of the retreat and disintegration of ice shelves around the Antarctic Peninsula during the last three decades and associated changes in air temperature, measured at various meteorological stations on the Antarctic Peninsula, are reviewed. The climatically induced retreat of the northern Larsen Ice Shelf on the east coast and of the Wordie, George VI, and Wilkins ice shelves on the west coast amounted to about 10 000 km2 since the mid-1960s. A summary is presented on the recession history of the Larsen Ice Shelf and on the collapse of those sections north of Robertson Island in early 1995. The area changes were derived from images of various satellites, dating back to a late 1963 image from the recently declassified US Argon space missions. This photograph reveals a previously unknown, minor advance of the northern Larsen Ice Shelf before 1975. During the period of retreat a consistent and pronounced warming trend was observed at the stations on both east and west coasts of the Antarctic Peninsula, but a major cause of the fast retreat and final collapse of the northernmost sections of the Larsen Ice Shelf were several unusually warm summers. Temperature records from the nearby station Marambio show that a positive mean summer temperature was reached for the first time in 1992-93. Recent observations indicate that the process of ice shelf disintegration is proceeding further south on both sides of the Antarctic Peninsula.
Keywords: Antarktis; brehylle; glasiologi; isbrem; isshelf; klimaendringer; meteorologi; satellittbilder

Report of the Norwegian Antarctic Research Expedition 1997/98 - Tveraa, Torkild (ed.); Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1999)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1997/98; biologi; geodesi; glasiologi; oseanografi

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

Ice sheet history from Antarctic Continental Margin sediments: The ANTOSTRAT approach - Barker, Peter; Barrett, Peter; Camerlenghi, Angelo; Cooper, Alan; Davey, Frederick; Domack, Eugene; Escutia, Carlota; Kristoffersen, Yngve; O'Brien, Philip (Terra Antarctica, 1998)
Keywords: Antarktis; glasiologi; innlandsis; sedimentologi

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Mass balance and dynamics on Jutulstraumen ice stream - Hagen, Jon Ove; Melvold, Kjetil (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isshelf; isstrøm; klimaendringer; snø

Study of velocity, mass flow and deformation in Jutulstraumen - Høydal, Øyvind Armand (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isstrøm

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Mass balance and dynamics on Jutulstraumen ice stream, NARE 1996/97 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Rolstad, Cecilie (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; isstrøm

Airborne radar soundings of ice depth, GPS measurements of ice velocity and studies of landform evolution in central Dronning Maud Land East Antarctica - Näslund, Jens Ove (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isstrøm; topografi

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Hot water drilling near Filchner station, Ronne ice shelf - Orheim, Olav; Østerhus, Svein; Melvold, Kjetil; Eiken, Trond; Thomsen, Henrik Højmark; Winther, Jan-Gunnar; Bævre, Halvor (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Antarktis; NARE 1992/93; glasiologi; havstrømmer; isshelf; oseanografi; vannmasser

Spatial distribution of snow in western Dronning Maud Land, East Antarctica, mapped by a ground-based snow radar - Richardson, Cecilia; Aarholt, Eldar; Hamran, Svein-Erik; Holmlund, Per; Isaksson, Elisabeth (Journal of Geophysical Research: Solid Earth, 1997)
During the austral summer 1993/1994, the spatial distribution of snow was mapped by a ground-based snow radar (800–2300 MHz) in western Dronning Maud Land, East Antarctica. Snow radar soundings were performed along continuous profiles extending from the ice shelf up to the polar plateau, a total distance of 1040 km. The high-resolution radar registrations revealed subsurface layering in the uppermost 12 m of the snowpack. The travel time record was translated into snow accumulation expressed in water equivalents, based on an empirical relationship between wave speed and firn density. A good knowledge on snow density variations with depth is essential for the variability studies. Generally, the snow layering was well developed in the coastal area and less well developed on the polar plateau. High spatial variability in snow accumulation was observed on a regional as well as on a local scale. The variability was very high in areas with large surface slopes, such as the grounding zone and around nunataks. The highest variability was recorded in the nunatak area, where the standard deviation reached 59% of the spatial average accumulation. On the smooth high-altitude plateau, variations in accumulation were less pronounced. However, here the standard deviation exceeded 22% of the average accumulation rate. Provided that the snow radar soundings are supported by dating of reference horizons along the travel route, this is a good method to obtain the accumulation rate and pattern for large areas with a high spatial resolution.
Keywords: Dronning Maud Land; fysisk geografi; geofysikk; geokjemi; glasiologi; iskjerner

Convergent flow of ice within the Astrolabe subglacial basin, Terre Adélie, East Antarctica: an hypothesis derived from numerical modelling experiments - Siegert, Martin J; Glasser, Neil F (Polar Research, 1997)
Keywords: Antarktis; geologi; geomorfologi; glasiologi; innlandsis; subglasial innsjø

Changing mass balance of the Filchner ice shelf due to climate variations - Solås, Monica Kristensen; Eggenfellner, Heinrich (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isshelf; klimaendringer

A stable isotope pilot study from blue ice areas at Jutulsessen, Dronning Maud Land, Antarctica - Thomsen, Henrik Højmark; Hagen, Jon Ove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; innlandsis; isbre; klimaendringer

Spectral reflectance of snow and glacier ice as measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; isbre

Report of the Norwegian Antarctic Research Expedition 1996/97 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1996/97; biologi; geodesi; geologi; glasiologi; oseanografi

Mass balance and dynamics on Jutulstraumen ice stream during NARE 1993/94 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Tonning, Tore (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; isstrøm

Report of the Norwegian Antarctic Research Expedition 1993/94 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1996)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1993/94; geodesi; glasiologi; ornitologi

Glaciological measurements at Jutulgryta - Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir; Bøggild, Carl Egede (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi

Spatial and temporal patterns in snow accumulation, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Journal of Glaciology, 1994)
During the Swedish Antarctic Expedition to Dronning Maud Land, Antarctica, 1988–89 the net accumulation was estimated for an area from the coast to about 400 km inland. Stake measurements were used to obtain the spatial variability and firn cores were used for the temporal variability. The mean annual accumulation for the period 1976–88 is about 0.4mw.e. for Riiser-Larsenisen and about 0.3mw.e. for the area above the grounding line. The accumulation rate at higher altitudes, > 2500 m a.s.1., is about 0.1 m w.e. for 1955–88. One record from the ice shelf covers the period 1957–88, and suggests an increase in accumulation of about 12%. Between 1976 and 1988, the accumulation has decreased by about 50%, most likely due to lower temperatures as suggested by the temperature record from Halley.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Report of the Norwegian Antarctic Research Expedition 1991/1992 - Østerhus, Svein (ed.) (Norsk Polarinstitutt, 1994)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1991/92; fugler; geologi; glasiologi; ornitologi; oseanografi

Oceanographic and glaciologic investigations through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; glasiologi; oseanografi

Proximal sub ice-shelf sedimentation Jutulgryta, East Antarctica - Solheim, Anders (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; glasiologi; isshelf

Spectral bi-directional reflectance of snow and glacier ice measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Annals of Glaciology, 1994)
Visible and near-infrared spectral reflectances of snow and superimposed ice were measured in Dronning Maud Land, Antarctica, during the 1992-93 austral summer. Spectral-reflectance curves of both snow and superimposed ice remain high ( > 80%) in the visible region. A pronounced decrease in reflectance appears in the near-infrared, especially for superimposed ice. Superimposed ice with a 1 cm thick surface layer of ice-bound snow crystals had a considerably higher reflectance than superimposed ice containing only a few snow crystals. Furthermore, these data prove that snow and superimposed ice reflect solar radiation specularly and suggest that the anisotropy strengthens with increasing wavelengths. Integrated in-situ reflectances corresponding to Landsat TM bands 1-4 show that TM band 1 is least affected, whereas TM band 4 is most affected by anisotropy. Furthermore, the anisotropy increases with increasing off-nadir viewing angles up to an angle corresponding to 90°-θs (θs = solar elevation). For a 15° off-nadir sensor-observation angle, the average snow reflectance for TM bands 1–4 is about 10% higher than at nadir. Similarly, the apparent reflectance can be more than 50% higher than the nadir reflectance for larger observation angles. Consequently, if satellite-derived reflectances are going to be considered as absolute values, a topographic-correction model is needed to correct for the effects of anisotropy.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Do glaciers tell a true atmospheric CO2 story? - Jaworowski, Zbigniew; Segalstad, Tom Victor; Ono, Nobuo (Science of The Total Environment, 1992)
Until 1985 most studies of CO2 in gas inclusions in pre-industrial ice indicated that CO2 concentrations (up to 2450 ppm) were higher than the current atmospheric level. After 1985, lower pre-industrial CO2 values were reported, and used as evidence for a recent man-made CO2 increase. The errors in these revised values, however, are of a similar magnitude to the apparent increase in atmospheric CO2 level. The assumptions used in estimating lower CO2 values in past atmospheres have been: no liquid phase in polar ice; younger age of air than of ice due to free gas exchange between deep firn and the atmosphere; and no change in composition of air inclusions. These assumptions are shown to be invalid. Liquid saline water exists in ice at low temperatures, even below −70°C; airtight ice layers are ubiquitous in Antarctic firn; and more than 20 physico-chemical processes operating in situ and in ice cores contribute to the alteration of the chemical composition of air inclusions. The permeable ice sheet with its capillary liquid network acts as a sieve which redistributes elements, isotopes, and micro-particles. Thirty-six to 100% of air recovered from old ice is contaminated by recent atmospheric air during field and laboratory operations. The value of ∼290 ppm, widely accepted from glacier studies for the pre-industrial atmospheric CO2 level, apparently results from: invalid assumptions; processes in ice sheets; artifacts in ice cores; and arbitrary rejection of high readings. To date, glaciological studies are not able to provide a reliable reconstruction of either the CO2 level in pre-industrial and ancient atmospheres or paleoclimates. Instead these studies have led to a widely accepted false dogma of man-made climatic warming. This dogma may have enormous negative impact on our common future.
URL: https://www.researchgate.net/publication/223504148_Do_glaciers_tell_a_true_atmospheric_CO2_story
Keywords: Antarktis; drivhuseffekt; glasiologi; global oppvarming; isbreer; karbondioksid; paleoklimatologi; stabile isotoper

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi